Social Capital as A Factor of Social Cohesion Introduction - Yuldashev Behzod Ruzimatovich (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2026)
This article provides a socio-philosophical analysis of the role and significance of social capital in ensuring social cohesion within society. The study examines the mechanisms of social capital formation in the context of socio-economic and political reforms being implemented in New Uzbekistan, highlighting its role in fostering social trust, cooperation, and civic engagement. The main components of social capital – social networks, norms and values, mutual trust, and solidarity relations – are considered as key factors that strengthen social stability and social cohesion. The article also analyzes the factors influencing the development of social capital under conditions of globalization and social transformations, and proposes scientific and practical conclusions aimed at reinforcing it. The research findings are of significant importance for strengthening social cohesion, developing civil society, and ensuring sustainable social development